ASSOCIATION BETWEEN IGE SERUM LEVEL AND SEVERITY OF ASTHMA IN CHILDREN - Nindy Resti Rahayu; Agung Prasetyo Wibowo; Muchammad Fahrul Udin; Ery Olivianto; Wisnu Barlianto; HMS. Chandra Kusuma (UNEJ e-Proceeding)
Asthma is an inflammatory chronic process involvingrespiratory tract wall and cause limited airflow withincreased of respiratory tract reactivity. It is arespiratory disease that is more common in children.Definition of asthma from Global Initiative Asthma(GINA), asthma is a heterogeneous disease, usuallymarked by chronic inflammation respiratory tract.Asthma causes symptoms such as wheezing,shortness of breath, chest tightness and cough thatvary over time, in their occurrence, frequency andintensity (GINA, 2016). International Consensus on(ICON) Pediatric Asthma, asthma is a chronicinflammation disorder which correlate withrespiratory tract obstruction that clinicalmanifestation wheezing, cough and shortness ofbreath (Rahajoe et al, 2015). Estimate prevalence ofasthma in the world is 7.2% (6% adults and 10%children) (Rahajoe, 2015).The pathogenesis, immunopathology, genetic,clinical manifestation, diagnosis and therapy forasthma had much progress. Therefore, it’s can’t besure which one comes first because the complexityof both factor (Rahajoe, 2015). In many case,especially children and young adult, asthma iscorrelated with manifestation of atopy in Ig-Edependentmechanism (Rahajoe, 2013). There wasno different of asthma mechanism in pediatric andadult. Although there was some problem in asthmapediatric there was not found in adult because of thepathology, lack of good scientific evidence,difficulties in determining of diagnosis and therapyand also variation of remodeling response of therapythat could not predicted before. This conditionespecially for children under five year old (Rahajoe,2015).In population, atopy factor give contribute 40%asthma patient pediatrics and adult. Atopy, thegenetic predisposition for the development of anImmunoglobulin E (IgE)-mediated response tocommon aeroallergens, is the strongest identifiablepredisposing factor for developing asthma (Rahajoe,2013). Asthma has an inheritable component to itsexpression, but the genetics involved in the eventualdevelopment of asthma (Ober, 2005). The role ofgenetics in IgE production, airwayhyperresponsiveness, and dysfunctional regulationof the generation of inflammatory mediators hasappropriately captured much attention. Asthma is aneffect from histamine in bronchial muscle. Histaminerelease together with IgE which mediated mast celldegranulation and make quickly contriction andbronchioles muscle spasm (Boyce, 2003). Ig Eattaches to cell surfaces via a specific high-affinityreceptor. The mast cell has large numbers of IgEreceptors; these, when activated by interaction withantigen, release a wide variety of mediators to iniateacute bronchospasm and also to release proinflammatorycytokines to perpetuade underlyingairway inflammation (Sporik, et al. 1995). Inlaboratory findings, pediatric patients with asthmashow increased IgE serum levels compared tonormal individuals without asthma. Ig E serum levelis specific for allergic status. It is useful to identifiedrisk factor or triggers of asthma. That is Ig Eresponsible for allergic attack (Rahajoe, 2013).However, lack of evidence of the associationbetween IgE serum levels and severity of asthma inchildren. This study aims to determine theassociation between IgE serum levels and severity ofasthma in children.